2015
DOI: 10.1080/15389588.2015.1042577
|View full text |Cite
|
Sign up to set email alerts
|

Serious road injuries in The Netherlands dissected

Abstract: The characteristics of serious road injuries differ from those of fatalities and the distribution of injuries over the body differs by travel mode, gender, and age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 22 publications
5
19
1
Order By: Relevance
“…and police reported data was observed in previous studies (Juhra et al 2012). The most relevant body regions were the same in both datasets and are in line with previous studies (Otte et al 2012;Weijermars et al 2016). In future studies, the risk of permanent medical impairment (Malm et al 2008) should be also considered additionally to the analysis of AIS severities.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…and police reported data was observed in previous studies (Juhra et al 2012). The most relevant body regions were the same in both datasets and are in line with previous studies (Otte et al 2012;Weijermars et al 2016). In future studies, the risk of permanent medical impairment (Malm et al 2008) should be also considered additionally to the analysis of AIS severities.…”
Section: Discussionsupporting
confidence: 88%
“…While other studies have mainly focused on the relevance of different injuries according to Abbreviated Injury Scale (AIS) body regions (Fredriksson and Rosen 2012;Otte et al 2012;Weijermars et al 2016), the current study was carried out to investigate injuries in more detail. The aim was to identify which injuries were most common in different databases.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the burden of injury body profiles between the countries are partly due to differences in the distribution of casualties over transport modes. of injuries and in the total burden of injury in the Netherlands for example is due to a relatively high number of bicycle (only) crashes (Weijermars et al, 2016b). Table 5 shows the average burden per MAIS3+ casualty for the different transport modes.…”
Section: % -5% 5% -10%mentioning
confidence: 99%
“…However, road traffic crashes also cause a large number of non-fatal (serious) road traffic injuries, resulting in considerable economic and human costs (Weijermars, Bos, & Stipdonk, 2016b). Moreover, the number of serious road traffic injuries has not been decreasing as fast as the number of fatalities in some countries, and has even been increasing in other countries (Berecki-Gisolf et al, 2013; OECD/ITF, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…One factor which plays a role is their relatively high vulnerability. In an accident, a senior cyclist runs a high risk of fracturing a hip or leg (Weijermars, Bos & Stipdonk, 2016). Electric vehicles can be expected to pose a safety threat particularly for the elderly due to their vulnerability and the difficulty this age group has with detection (Mendonça et al, 2013) and localisation (as shown in this study) of electric vehicles.…”
Section: Implications For Cycling Safetymentioning
confidence: 60%